QUALITY OF LIFE AND PHYSICAL ACTIVITY AMONG LOWER LIMB AMPUTEES VISITING PHYSICAL REHABILITATION CENTRE, UNIVERSITY OF MAIDUGURI TEACHING HOSPITAL, NIGERIA (Journal of Biomedical Investigation, 2025)
Background: Lower limb amputees usually have reduced mobility which affects their capacity to carry out daily tasks and physical activity which greatly affects their quality of life (QoL).Aim: This study determined the QoL, physical activity and their associations with demographic and clinical factors of lower limb amputees at University of Maiduguri Teaching Hospital.Methods: This was a cross-sectional survey involving fifty amputees recruited through a convenience sampling technique. Quality of life was assessed using the WHOQOL-Bref (Hausa version) while physical activity (PA) was assessed using the International Physical Activity Questionnaire (IPAQ)- short form (Hausa version). Socio-demographic information of age, gender, level of education, and clinical factors such as cause of amputation, level of amputation and time since amputation were also obtained. Data were analysed by descriptive statistics and inferential statistics of Chi-square (ꭓ2 ) test. Statistical significance was set at p
Keywords: Quality of Life; Physical activity; Lower limb; Amputation; Physical Rehabilitation Centre; Northeastern Nigeria